Development Policy in Africa - Kararach, G. author. aut Link
X, 335 p.
Keywords: The author investigates the agenda for transformation in contemporary African development studies: policy studies, strategic studies, international relations and economic diplomacy. With a focus on the capacity dimension, he proposes critical policy and action-oriented recommendations on how to overcome present and future emergencies in Africa.